NLR, d-NLR and PLR can be affected by many factors - Bedel, Cihan (Int Immunopharmacol, 2021)
We have read the article by Yang et al, entitled “The diagnostic and predictive role of NLR, d-NLR and PLR in COVID-19 patients” with great interest. The authors emphasized that the NLR (Neutrophil to lymphocyte ratio) is an independent prognostic biomarker for COVID-19 patients. First of all, we congratulate the authors for their valuable contribution to the literature in these difficult conditions. However, we would like to add on a few cases that need more attention.